Design and Optimization of Brushless Hybrid Wound Rotor Vernier Motor for Variable Speed Applications - Kapeel Kumar; Qasim Ali; Sheeraz Ahmed; Muhammad Ilyas; Hanlin Zhan; Mudassir Raza Siddiqi (IEEE Access)
This paper presents the optimized design and electromagnetic performance analysis of a brushless hybrid wound rotor vernier motor (BL-HWRVM) for automatic washing machine applications. The automatic washing machine has two operating cycles: the wash cycle at low speed and the spin dry cycle at high speed. The proposed machine utilizes a different winding configuration that improves the performance as compared to the existing reference machine. The machine configuration utilizes two different windings on the stator. One is a three-phase main ABC winding, and the other is a single-phase additional X winding. Both windings are designed in such a way that they generate both fundamental and subharmonic components of MMF in the air gap of the machine. In order to excite the rotor field winding using a brushless excitation technique, an additional excitation winding is placed on the rotor, which is connected through a rotating rectifier to the field winding. The voltages are induced in this excitation winding using the sub-harmonic component of the MMF. These AC-induced voltages are rectified by a rotating rectifier and are then fed to the field winding. A 4-pole-24-slot stator and 44-pole-44-slot outer rotor motor is designed. To reduce the torque ripple in the BL-WRVM 3-degree of skew angle is implemented on the rotor. To improve the value of average torque, a new hybrid model is designed and proposed by placing small magnets on the rotor. To find out the optimal shape of the magnets, the Genetic algorithm optimization technique is used. Finally, the performance of all the designs is compared. The proposed BL-HWRVM demonstrates a 9.47% efficiency improvement in washing mode and an 11.84% efficiency improvement in spin-dry mode compared to the reference machines.